Exploring the Interaction Effects of Gender Contentedness and Pubertal Timing on Adolescent Longitudinal Psychological and Behavioral Health Outcomes - Kuo, Jen-Hao; Albaladejo Carrera, Raúl; Cendra Mulyani, Lidya; Strong, Carol; Lin, Yi-Ching; Hsieh, Yi-Ping; Tsai, Meng-Che; Lin, Chung-Ying (Frontiers in Psychiatry, 2021)
Background Off-time pubertal timing (PT) and nonconforming gender identity have been reported to predict adverse health and wellbeing in adolescents. However, the joint effects of these two factors are less addressed. We aimed to investigate the main and interaction effects of gender identity, proxied by perceived gender contentedness (GC), and PT on longitudinal adolescent psychological and behavioral outcomes. Methods Data (N=1806, Mage = 13.3 ± 0.5 years) come from the Taiwan Youth Project, which prospectively followed a longitudinal cohort of Taiwanese junior high school students from 2000 (wave 1) to 2009 (wave 9). GC was self-reported at waves 1 and 9 in a binary response, and thus 4 GC trajectories were created. PT was defined using the Pubertal Developmental Scale, which mainly measured physical changes in puberty. Multiple linear regression analyses with gender stratification were applied to examine the effects of the GC trajectory and its interaction with PT on the outcomes. Results A total of 1,562 subjects (86.5%) remained consistently satisfied with their gender, while the GC of 226 subjects (12.6%) changed at some point. Regression analyses found that males with gender dissatisfaction at wave 9 were likely to engage in delinquent behavior, and females in this group were more likely to have lower self-esteem, as compared to those with consistent GC. The interaction effect between the GC trajectory and PT appeared to be associated with smoking and drinking only at wave 1. Conclusions These findings indicate that healthcare professionals should concentrate on gender nonconforming individuals at early adolescence, navigating them toward a healthy adulthood.